Climatic change and human-marine interactions in the uttermost tip of South America in Late Holocene. (30th May 2020) - Álvarez, Myrian; Briz i Godino, Ivan; Pal, Nélida; Bas, Maria; Lacrouts, Adriana
Abstract: Palaeoclimatic records from southern tip of South America during the Last Holocene, indicate important climate intervals, such as the Medieval Climate Anomaly and Little Ice Age, which offered new scenarios to hunter-gatherer groups who inhabited the region. The aim of this paper is to explore the social practices carried out by hunter-fisher-gatherer societies of the southern part of the Atlantic Coast of Tierra del Fuego island (53–55°S, 66–74°W) in order to deal with these environmental changes. From our perspective, foragers have played an active role in designing strategies to cope with environmental fluctuations. Consequently, we argue that in a context of ecological uncertainty, these societies would have developed flexible strategies in terms of subsistence, technology and settlement patterns. In order to test this proposal, zooarchaeological and technological analysis of different archaeological assemblages dated between the 1300 to 220 BP were undertaken. The results show that these hunter-fisher-gatherer societies exploited a broad range of faunal resources using a versatile technology which encompassed tools with low production values and high use values. Likewise, the analysis of landscape organization revealed a settlement strategy centered on the most productive habitats, which were preferentially reoccupied. We suggest that these strategies, supported by cumulative knowledge and material conditions, could have enhanced social resilience and sustainability.